Analisis Pengaruh Ekonomi Makro terhadap Pertumbuhan Pembiayaan Syariah di Indonesia - Dewi Safitri; Sofi Abdurazzaq; Hendi Fauzi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This article aims to analyze the influence of macroeconomic variables on the growth of Islamic financing in Indonesia. The growing Islamic financing in Indonesia's financial sector requires a deeper understanding of the macroeconomic factors that influence its performance. This study uses a quantitative approach with regression analysis to identify the relationship between inflation, interest rates, exchange rates, and gross domestic product (GDP) on the growth of Islamic financing. The data used in this study are sourced from the Central Bureau of Statistics (BPS) and the Financial Services Authority (OJK) in the period 2010 to 2023. The results of this study are expected to provide insights for policy makers and financial practitioners in managing Islamic financing in Indonesia.